RISK FACTORS OF DENGUE MORTALITY IN PAMEKASAN DISTRICT (2018-2020) - Shavia Maulidina Zein; Yunus Ariyanto; Arina Mufida Ersanti (Jurnal Berkala Epidemiologi, 2022)
Background: The incidence of Dengue Haemoragic Fever (DHF) in the Pamekasan District is still high. Mortality of DHF was always happening in Pamekasan District from 2016 to 2020. Purpose: This study aims to analyze the risk factors of DHF mortality in the Pamekasan District (2018-2020). Methods: The study was conducted from October 2020-June 2021 with a case-control study. Total population was 293 cases. The sample was 54 respondents (1:2) with proportional random sampling. The inclusion criteria were families living under the same roof for a minimum of 17 years. The variables were dengue mortality, age, sex, education, history of DHF, comorbidities, access to health services, delay in treatment, family income, residence, and family knowledge. Data were collected through interviews and documentation study. The analysis in this study used univariate (frequency) and bivariate (crosstabs use OR). Results: Risk factors of DHF mortality in Pamekasan District are children (OR = 2.05; 95% CI=0.59-7.04), low education (OR=1.16; 95% CI=0.30-4.46), history of dengue (OR=3.57;95%CI=1.09-11.66), comorbidities(OR=17.50; 95% CI=4.25-72.05), difficult access to health services (OR=3.10; 95% CI=0.79-12.09), delay in treatment (OR=5.20;95% CI=1.50-18.0), low income family (OR=1.16; 95% CI = 0.30-4.46) and low of family knowledge about dengue (OR = 7.00; 95% CI = 1.99-24.58). Meanwhile, protective factors are female (OR = 0.70; 95% CI = 0.22-2.23) and rural (OR = 0.48 ; 95% CI = 0.13-1.73). Conclusion: Risk factors of DHF mortality in Pamekasan District (2018-2020) are the history of DHF, comorbidities, delay in treatment, and low family knowledge about DHF.   ABSTRACT Background: The incidence of dengue fever in Pamekasan District is still high. Mortality of dengue was always happen in Pamekasan District since 2016 to 2020. Purpose: This study aimed to analyze the risk factors of dengue mortality in Pamekasan District (2018-2020). Methods: This research was case-control study. The study was conducted from October 2020-June 2021 in Primary Health Care selected at Pamekasan District. Total sample was 54 cases. Data was collected by interviews and documentation study. Analysis using uinvariate and bivariate (OR test).  Results: Based on the results of OR test,  risk factors of dengue mortality in pamekasan district (2018-2020) are: children (OR = 2.05 ; 95% CI = 0.59-7.04), education ≤ 9 yeras (OR = 1.16; 95% CI= 0.30-4.46), history of dengue (OR= 3.57 ; 95% CI = 1.09-11.66), comorbidities (OR=17.50; 95% CI=4.25-72.05), difficult access to health services (OR=3.10; 95% CI=0.79-12.09), delay in treatment (OR=5.20 ; 95% CI = 1.50-18.0), low income family (OR = 1.16; 95% CI = 0.30-4.46) and low of family knowledge about dengue (OR = 7.00; 95% CI = 1.99-24.58) while protective factors are : female (OR = 0.70; 95% CI = 0.22-2.23) and rural areas (OR = 0.48 ; 95% CI = 0.13-1.73). Conclusion: Risk factors of dengue mortality in Pamekasan District (2018-2020) are history of dengue, comorbidities, delay in treatment and low of family knowledge about dengue.